Does the activity of the proteasome decline during human ageing and in the brains of Parkinson’s disease patients? - Wayne, Declan (2018)
Background: It is well documented that the global population is steadily rising. A major factor for the rising population is the increase in life expectancy. As medical advancements are, made we are now living longer than at any point in human history. As a result of this, levels of neurodegeneration are at an all-time high and propose a significant health burden. Parkinson ’s disease (PD) is the world’s second most prevalent neurodegenerative disease, which has its pathology linked to a range of complex interactions resulting in accumulation of protein aggregates, increased cellular oxidative stress, impaired mitochondrial function and dysfunction within the cellular maintenance systems, the ubiquitin proteasome system (UPS) and the lysosomal degradation pathway. This project aims to assess potential decline in UPS activity in PD and in conventional ageing, whilst also investigating dysregulation of important homeostatic cellular proteins as a result of oxidative stress.